Sustainable treatment of rubber latex processing wastewater : the UASB-system combined with aerobic post-treatment - Nguyễn, Trung Vệt (Wageningen Universiteit, 1999)
The mainof this thesis is to assess the applicability of UASB process for treating RLP wastewater and the feasibility of some adequate post-treatment processes for the effluent of the anaerobic treatment process.